New records of Caddisflies (Insecta: Trichoptera) from India - Pandher, Manpreet Singh; Kaur, Simarjit; Garima, Deepti; Dubey, Anil Kumar (Zootaxa, 2021)
Four species of Trichoptera are recorded for the first time from the geographical limits of India: Oecetis jacobsoni Ulmer 1930 and Marilia ceylanica Martynov 1936 (both from the Andaman & Nicobar Islands Union Territory of India), Polyplectropus amphion Malicky 1997a from West Bengal, and Polyplectropus phrixos Malicky & Changthong 2006 (in Malicky et al. 2006) from Mizoram, respectively. Line drawings of all the newly recorded species and Hydropsyche saranganica Ulmer 1951 are given based on material collected from the geographical limits of India.